Emergence of fluoroquinolone-resistant Escherichia coli at a cancer center. - Kern, W V (1994)
Prophylactic treatment with fluoroquinolones of patients with profound neutropenia has been found to be useful for preventing gram-negative bacteremia and has become a standard preventive-therapy strategy in many cancer centers, but the development of bacterial resistance is a cause of concern. During the past few years, we have observed an increasing number of patients with leukemia from whom fluoroquinolone-resistant strains of Escherichia coli were isolated. The increase was significant in this patient population, and among patients with other underlying diseases, the rates of isolation of such strains per number of discharges were significantly lower and did not increase. Most of the leukemia case patients (16 of 19) had been pretreated with an oral quinolone (ofloxacin), with cumulative doses until the first isolation of a resistant E. coli strain ranging from 0 to 97.8 g (median, 14.4 g). Repeated isolation of such strains was seen in 8 of 17 patients during a follow-up period of > or = 4 weeks and in 1 of 6 patients during a follow-up period of > or = 16 weeks. Ten patients developed bacteremia (mortality, 1 of 10). On the basis of the number of patients with leukemia admitted to the hematology-oncology service, the incidence of bacteremia caused by fluoroquinolone-resistant E. coli increased from < 0.5% in 1988-1989 and 0.8% in 1990-1991 to 4.5% in 1992-1993 (P < 0.01). MICs for nine isolates obtained from cultures of blood from different patients ranged between 8 and 16 microgram/ml (ciprofloxacin and PD 131628), 8 and 32 microgram/ml (ofloxacin and BAY Y 3118), and 16 and 32 microgram/ml (sparfloxacin) and indicated resistance to trimethoprim-sulfamethoxazole, ampicillin, doxycycline, and chloramphenicol. Of nine isolates obtained from cultures of blood from different patients and that were subjected to genomic DNA typing by pulsed-field gel electrophoresis of XbaI digests, seven were typeable. Among these, four different genotypes were identified, suggesting both the independent development and the horizontal spread of resistant clones of E. coli.